DEVELOPMENT OF COMPOSITION AND PRODUCTION TECHNOLOGY FOR POLYMER-BITUMEN MIXTURES FOR AUTOMOBILE ROADS - Ikromov, M (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article highlights that the modification with varying amounts of organomineral modifier primarily improves parameters that lead to an increased service life of road bitumens, as supported by data obtained from experimental studies. It has been established that the softening and freezing temperatures of the polymer-bitumen composition are altered by adding thermomechanically ground powder of worn-out rubber products based on styrene-butadiene and isoprene rubbers. This addition is made at high temperatures, utilizing active organic compounds present in the modified bitumen.